2001
DOI: 10.1292/jvms.63.135
|View full text |Cite
|
Sign up to set email alerts
|

Negative Inotropic Effect of Diazepam in Isolated Guinea Pig Heart.

Abstract: ABSTRACT. The inotropic effect of diazepam, a benzodiazepine derivative, and its mechanism of action were examined using guinea pig heart and single ventricular cell preparations. In Langendorff hearts and right ventricular free-wall preparations, diazepam (10 to 100 µM) produced a monophasic negative inotropic effect in a concentration dependent manner. Neither a central type (flumazenil 1 µM) nor a peripheral type (PK11195 10 µM) of benzodiazepine receptor antagonist antagonized the monophasic negative inotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…521 Four studies indicated that flumazenil is unlikely to improve hemodynamic function in the setting of benzodiazepine overdose and may complicate other therapy (LOE 5). 518,[522][523][524] Two studies described serious adverse effects such as seizure, arrhythmia, hypotension, and withdrawal syndrome after flumazenil was given to patients presenting with decreased level of consciousness attributed to either benzodiazepine toxicity or an unknown cause (LOE 5). 518,525 These side effects were more common with coingestants (such as tricyclic antidepressant and opioids), chronic benzodiazepine use or abuse, and known seizure disorder.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…521 Four studies indicated that flumazenil is unlikely to improve hemodynamic function in the setting of benzodiazepine overdose and may complicate other therapy (LOE 5). 518,[522][523][524] Two studies described serious adverse effects such as seizure, arrhythmia, hypotension, and withdrawal syndrome after flumazenil was given to patients presenting with decreased level of consciousness attributed to either benzodiazepine toxicity or an unknown cause (LOE 5). 518,525 These side effects were more common with coingestants (such as tricyclic antidepressant and opioids), chronic benzodiazepine use or abuse, and known seizure disorder.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…For example, diazepam decreased the Ca 2+ transient and the L-type Ca 2+ channel, which are both important in the negative inotropism and chronotropism caused by this drug (27)(28)(29). In the same line, another study on guinea pigs' hearts indicated that the negative inotropic effect of diazepam referred to its calcium channel blocking effect (15). Ca 2+ , as a second messenger and a regulatory factor, plays a pivotal role in progression of cardiac hypertrophy (30).…”
Section: Discussionmentioning
confidence: 95%
“…Peripheral Benzodiazepine Receptors (PBRs), also known as 18kDa translocator proteins, are expressed in various tissues, including the heart, and play an important role in regulation of cardiac hypertrophy and IschemiaReperfusion (I/R) injury (3,(14)(15)(16)(17). Hence, they represent a novel therapeutic target in cardiovascular diseases (18).…”
Section: The Effect Of Diazepam On the Function Of Hypertrophied Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, both positive and negative inotropic actions, biphasic inotropic action, and no effect of diazepam have been reported in different species of animals using various ranges of concentrations [1,5,8,23]. Our previous studies have provided one explanation for this contradiction, i.e., diazepam produced the negative inotropic effect in isolated guinea pig heart through inhibition of the calcium current [15], while at the same time, it increased calcium sensitivity of the cardiac muscle fiber in the same concentration ranges [13]. From these reports about diazepam, benzodiazepine derivatives are presumed to affect the ionic currents in the heart.…”
mentioning
confidence: 95%